Solidarity beyond the grave: Yielding organs in a Nordic welfare state - Susanne Ådahl (Medicine Anthropology Theory, 2022)
According to a survey carried out in 2009, Finnish citizens are exceptionally willing to donate their organs after death, an attitude that paved the way for a 2010 amendment to the Tissue Law that introduced an ‘opt-out’ consent policy. Reactions to the legislative change ranged from taking a highly utilitarian stance on the issue to expressing indignation over the welfare state meddling with citizens’ right to self-determination and ownership of the body. In this article I consider how willingness to donate is linked to the notion that donation is a civic obligation, as well as a means to distribute the valuable national resource that organs are deemed to be. I explore how the welfare state relates to national attitudes towards donation, and I discuss culturally specific terms for donation as a way of understanding the emotions that surround it. By examining the rhetorical moves that turn the body into a community resource, I analyse the specifics of bodily citizenship in Finland, and particularly how the notion of solidarity can be used to explain citizens’ motivation to donate their bodies after death. A key finding is that solidarity is not only needed in order to bring about donation but also produced as a result of donation.